Sesamin protects SH-SY5Y cells against mechanical stretch injury and promoting cell survival - Xu, Zhiming (BMC Neurosci, 2017)
BACKGROUND: Sesamin is a well-known antioxidant extracted from sesame seeds that exhibits various curative effects. The present study investigated whether sesamin would protect neuroblastoma SH-SY5Y cells against mechanical stretch injury-induced increases in reactive oxygen species (ROS) and apoptosis. Additionally, the mechanisms underlying these actives were investigated. Following exposure to mechanical stretch injury, cells were incubated for further investigations. Lactate dehydrogenase and Cell Counting Kit-8 assays were used to assess cell viability, and a terminal deoxynucleotidyl transferase dUTP nick end labeling assay and flow cytometric analysis were performed to evaluate changes in mitochondrial membrane potential (ΔΨm). Furthermore, intracellular levels of ROS production were measured by 20, 70-dichlorofluorescein diacetate staining, the mRNA levels of matrix metallopeptidase 9 (MMP-9) were evaluated using real-time polymerase chain reaction analysis, and the determinations had also been made on related proteins by Western blot analysis. RESULTS: Exposure to mechanical stretch injury significantly decreased cell viability but this decrease was attenuated by pretreatment with sesamin (50 μM). Sesamin also significantly inhibited mechanical stretch injury-induced increases in intracellular ROS production, attenuated declines in ΔΨm, diminished the expressions of pro-apoptotic proteins, and decreased cell apoptosis. Stretch injury increased Bax and cleaved caspase 3 levels, enhanced the gene expression of MMP-9, increased the phosphorylation levels of Akt, p38, and JNK and decreased Bcl-2 levels in the cells. However, pretreatment with sesamin reduced the mechanical stretch injury-induced overexpression of MMP-9. CONCLUSIONS: Sesamin protected SH-SY5Y cells against stretch injury by attenuating increases in ROS levels and suppressing apoptosis. Accordingly, sesamin seems to be a potentially therapeutic agent in the treatment of traumatic brain injury. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12868-017-0378-8) contains supplementary material, which is available to authorized users.